Dans et hors la ville : esquisse d’une géographie des artistes plasticiens à Bruxelles (19e‑21e siècles) - Tatiana Debroux (Brussels Studies, 2013)
Based on detailed diachronic mapping, this article analyses artists’ areas of residence in Brussels from 1830 until today. Powerful spatial logic has taken shape over time, marking the appearance, decline and permanence of poles with a concentration of artists, which must be understood in the context of urban dynamics which have shaped the urban fabric. Three periods may be identified, corresponding to the development (or redevelopment) of specific areas in the city: the second half of the 19th century, associated with the urbanisation of artists’ suburbs in the northeast; the interwar period, characterised by concentrations on the outskirts; and the end of the 20th century, when the former southeast pole became popular once again, at the same time that new concentrations appeared in connection with the renovation of central areas. The mapping work and the results obtained provide an original view of the structuring of the artistic world in Brussels, while revealing the importance of a historical approach in the analysis of contemporary urban dynamics with artists in the spotlight.